2009
DOI: 10.3136/fstr.15.427
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Enrichment of Salmonella spp, Escherichia coli O157:H7, Vibrio parahaemolyticus, Staphylococcus aureus, Bacillus cereus, and Listeria monocytogenes by Single Broth and Screening of the Pathogens by Multiplex Real-time PCR

Abstract: Simultaneous enrichment broth (SEB) was developed for the single-enrichment simultaneous screening of six major food poisoning bacteria. After enrichment in SEB for 18 h at 37℃, viable counts of six major food poisoning bacteria (Staphylococcus aureus, Salmonella spp., Escherichia coli O157:H7, Vibrio parahaemolyticus, Bacillus cereus, and Listeria monocytogenes) were sufficient for 5' nuclease multiplex real-time PCR assay using existing primers and probes. By labeling the probes with three different fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
(20 reference statements)
1
17
0
Order By: Relevance
“…Several attempts have already been made to obtain recovery of multiple pathogens concurrently (Omiccioli et al 2009;Kim and Bhunia 2008;Kobayashi et al 2009) through the development or improvement of single enrichment broths. Such advances represent a promising alternative for future food quality analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have already been made to obtain recovery of multiple pathogens concurrently (Omiccioli et al 2009;Kim and Bhunia 2008;Kobayashi et al 2009) through the development or improvement of single enrichment broths. Such advances represent a promising alternative for future food quality analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These results were obtained by using the precipitates of sonicated samples and Biacore J. O157 at 1.8 × 10 6 CFU/mL, SE at 0.9 × 10 7 CFU/mL and LM at 1.8 × 10 7 CFU/mL produced positive signal changes of 39, 65, and 22 RU, respectively, and were significantly higher than those of the control samples. It has been reported that the cell concentration of O157, SE, and LM was less than 10 8 CFU/mL after the simultaneous enrichment of six foodborne pathogens, including these three pathogens (Kobayashi et al, 2009). Hence, the lower limit of detection using an SPR biosensor with specific PAbs for O157, SE, and LM was determined to be 1.8 × 10 6 , 0.9 × 10 7 , and 1.8 × 10 7 CFU/mL, respectively.…”
Section: Cross-reactivity Test On Supernatants and Precipitatesmentioning
confidence: 99%
“…Excellent results were obtained with the modified version of N17 broth with all the bacteria tested, obtaining colony counts higher than 10 6 CFU/ml for all microorganisms tested. Another non-selective enrichment broth recently developed is the simultaneous enrichment broth (SEB) developed by Kobayashi et al SEB was applied for the simultaneous recovery of Salmonella spp., L. monocytogenes, S. aureus, Bacillus cereus, Vibrio parahaemolyticus, and E. coli O157:H7; and its performance was compared to tryptic soy broth (TSB) (Kobayashi et al, 2009). Even though satisfactory results were obtained when compared against TSB, further studies need to be performed with natural and spiked food and environmental samples.…”
Section: Enrichment Brothsmentioning
confidence: 99%
“…Out of these, PrepMan Ultra® and InstaGene® have been extensively applied, especially with Gram negative bacteria. The DNeasy Tissue Kit is one of the most frequently selected kit as it has proven suitable for different types of samples and with different types of micro-organisms (Elizaquivel & Aznar, 2008;Elizaquível et al, 2011;Jofré et al, 2005;Kobayashi et al, 2009;McGuinness et al, 2009). …”
Section: Dna Extraction Protocolsmentioning
confidence: 99%
See 1 more Smart Citation